Panniculitis associated with amyopathic dermatomyositis - Azevedo, Paula de Oliveira (Sociedade Brasileira de Dermatologia, 2018)

(untitled) (An Bras Dermatol)
Panniculitis is a rare clinical finding in dermatomyositis, with less than 30 cases reported and there is only one case associated with the amyopathic subtype described in the literature. The present report describes a 49-year-old female patient that one year after being diagnosed with amyopathic dermatomyositis, presented indurated, painful, erythematous to violaceous nodules located on the upper limbs, thighs and gluteal region. Skin biopsy revealed lobular panniculitis with a lymphocytic infiltrate. The patient was treated with prednisone and methotrexate, but remained unresponsive to treatment.